Feasibility study on the influence of Taijiquan on the physical and mental health of the elderly in the Post-epidemic Era - Zhang, Jingjing (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: With the outbreak of the new coronavirus, a large number of studies have shown that due to the influence of age, the physical functions of the elderly are showing a downward trend, and their own immunity and external resistance are weaker than young people, and they are more susceptible to the new coronavirus. Respiratory tract infectious diseases, including viral pneumonia, have serious adverse effects on the mental and physical of the elderly. As my country’s aging degree continues to deepen, the sudden new type of coronavirus has brought a huge threat to the health of the elderly. During the outbreak of the new crown epidemic, the country has entered the home isolation stage. Due to the reduced range of activities, lack of self-exercise, and various internal and external factors, the elderly are more likely to develop depression and psychological symptoms, leading to symptoms such as low immunity. For infectious diseases such as new coronary pneumonia, the severity of the disease is closely related to the amount of virus infected and its own immune function. Therefore, the elderly are susceptible to infection and difficult to recover due to their age and physiological characteristics. This situation can be achieved by practicing Tai Chi. Boxing is gradually improved, so that the physical functions and emotions of the elderly can be well exercised and fully released, enhance the body’s immunity, prevent various bacterial, viral infections and epidemic diseases, strengthen the strength of respiratory muscles, and improve lung function. Reducing the incidence of respiratory tract infectious diseases is beneficial to the physical and mental health of the elderly. These effects of Taijiquan have potential positive effects in the elderly’s response to the new coronavirus infection, prevention and treatment. method: This article uses literature and logical analysis to analyze the feasibility study of Taijiquan’s impact on the physical and mental health of the elderly in the post-epidemic era, aiming to explore the positive effects of Taijiquan on the physical and mental health of the elderly, and summarize Taijiquan An effective way to improve the health of the elderly provides a theoretical basis and reference for the health protection of the elderly in the post-epidemic era. Results: Studies have shown that Tai Chi can relieve the elderly’s negative emotions such as anxiety and depression, reduce the incidence and mortality of various common diseases, and improve the quality of life and self-immunity of the elderly. Practicing Tai Chi has a positive effect on the health of the elderly, and it can play a positive role in improving the health of the elderly in the later stage of the epidemic. Conclusion: Through research, it is concluded that following the law of exercise and practicing Taijiquan step by step will help improve the health of the elderly under the conditions of normal epidemic prevention and control, and have a positive impact on the physical and mental health of the elderly. First of all, the elderly group practicing Tai Chi has a positive effect on the respiratory system. Taijiquan is mainly based on abdominal breathing, deep and slow breathing exercises under the guidance of the mind. At the same time, under the rhythm of music, the body movements are naturally combined with breathing to regulate the body’s various qi. The coordinated work between them promotes blood circulation and accelerates the speed of blood flow, so that various nutrients can be transported to the various organs of the body faster. The elderly can practice Tai Chi, adjust the breathing rhythm, and find a reasonable way of exercise; secondly, Practicing Taijiquan in the elderly group has a positive effect on the nervous system. All human activities are inseparable from the control of the nervous system, which is the center that regulates and innervates the activities of the body’s organs. Taijiquan exercises have a slow and gentle rhythm, which requires the coordination of the whole body to complete. The coordination of mind and breathing is used to control and coordinate the excitement and inhibition of the human nervous system. The elderly who have participated in Tai Chi exercises for a long time will not only improve their coordination ability, but also improve their nerve center function. At the same time, they can also prevent brain degeneration, enhance memory, relieve fatigue, and are common to sleep, chronic diseases and respiratory infections. The disease also has a better prevention and treatment effect, which can well enhance the body’s ability to fight foreign bacteria and viruses, and enhance the self-immunity and resistance of the elderly; again, Tai Chi helps to promote the thinking of the elderly and improve the memory. Tai Chi is a medium-to-small-intensity aerobic exercise that can effectively promote blood circulation throughout the body, enhance heart and lung function, strengthen brain metabolism, make the brain get more oxygen, and provide necessary material protection for the brain’s memory and thinking activities. Promote the development of the thinking of the elderly and enhance their memory; finally, Tai Chi helps the elderly to obtain a better emotional experience. With the faster and faster pace of social life, the elderly are more likely to produce some negative emotions, these emotions are not well vented, and Tai Chi exercise can calm the mind and relax the body, which can be well regulated. The body and mind of the practitioner helps people to experience the highest state of the spirit, thereby improving tension, releasing negative emotions, and relaxing the mind and body of the elderly. Traditional Chinese sports are representative of China’s excellent culture, such as Tai Chi, Baduan Jin, Yi Jin Jing, and traditional Qigong can all play a health promotion role. Analyze the positive impact and help that the elderly practicing Taijiquan brings to themselves under the new crown pneumonia epidemic, timely implement the positive effect of Taijiquan on the physical and mental health of the elderly, and gradually spread Taijiquan among the elderly, Vigorously popularize. Taijiquan combines rigidity and softness, evenly coordinated breathing and delicate movement rhythm. It is widely loved by the elderly and has a positive effect on the physical and mental health of the elderly.